Changes in a criminal statute during Kazakhstan to Russia (Journal of actual problems of jurisprudence, 2019)
In accordance with the aim of research in the article the criminal is examined legislation during tacking of Kazakhstanto Russia. During research the special attention is spared to the imperial legislation and Kazakh ordinary right. Duringthe analysis of imperial legislation opinion is grounded, that legal system of Kazakh society and his norm lost themeaningfulness also changed fully.Key words: crime, norm, law, charter, politics, legal norm.